2019
DOI: 10.1167/iovs.18-25536
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Activity of Mitochondrial Proteins in Vascular and Avascular Retinas: Implications for Retinal Metabolism

Abstract: PURPOSE. Understanding the energetics of retinal neurons and glia is crucial for developing therapies for diseases that feature deficits in nutrient or oxygen availability. Herein, we performed a detailed characterization of the distribution and activity of mitochondrial proteins in the vascularized retinas of rat and marmoset, and the avascular retinas of rabbit and guinea pig. Further, we delineated expression of ubiquitous mitochondrial creatine kinase (uMtCK). METHODS. Expression of eight mitochondrial pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…We have recently shown that in vascularized retinas (marmoset and rat) the IPL displays intense punctate immunoreactivity for mitochondrial proteins. (Chidlow et al, 2019) Conversely, in the avascular retina (rabbit and guinea pig), intense labeling of photoreceptor inner segments was observed, but the inner and OPL display only weakly punctate staining, indicating that avascular retinas are generating ATP via nonaerobic glycolytic mechanisms. Enzyme histochemistry assays for three mitochondrial enzymes were also consistent with this pattern.…”
Section: Energy Metabolism Of Rgc Dendritesmentioning
confidence: 97%
See 2 more Smart Citations
“…We have recently shown that in vascularized retinas (marmoset and rat) the IPL displays intense punctate immunoreactivity for mitochondrial proteins. (Chidlow et al, 2019) Conversely, in the avascular retina (rabbit and guinea pig), intense labeling of photoreceptor inner segments was observed, but the inner and OPL display only weakly punctate staining, indicating that avascular retinas are generating ATP via nonaerobic glycolytic mechanisms. Enzyme histochemistry assays for three mitochondrial enzymes were also consistent with this pattern.…”
Section: Energy Metabolism Of Rgc Dendritesmentioning
confidence: 97%
“…Enzyme histochemistry assays for three mitochondrial enzymes were also consistent with this pattern. (Chidlow et al, 2019)…”
Section: Energy Metabolism Of Rgc Dendritesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that the axon volume is estimated to comprise 80% of the total RGC volume based on published data [127,153,169], and the lack of saltatory conduction in the unmyelinated intraocular portion of the RGC axons both place a particular bioenergetic burden on this cellular component. While the cell soma is the principal site for energy production and protein synthesis, there is evidence that the axons supplement some of these functions as they share a similar mitochondrial profile with the somata [170].…”
Section: Energy Metabolism In Rgc Axonsmentioning
confidence: 99%
“…Functions ascribed to the creatine kinase/phosphocreatine kinase system include spatiotemporal buffering of ATP and improving the efficiency of oxidative phosphorylation. The creatine transporter, which is responsible for creatine uptake into cells, and creatine kinase, which catalyzes the reversible conversion of creatine into high energy phosphocreatine, are both expressed in photoreceptors (Acosta et al, 2005; Linton et al, 2010; Rueda et al, 2016; Chidlow et al, 2019); thus, supplementation with creatine is a neuroprotective strategy worthy of investigation.…”
Section: Introductionmentioning
confidence: 99%